Visit of Prime Minister Dr. Manmohan Singh to Kuala Lumpur for the India-ASEAN Summit, 11-14 December 2005. - Manmohan Singh 1932- (External Publicity Division, Ministry of External Affairs, 2005)
Includes report of the First East Asia Summit held on 13-14 December 2005 in Kuala Lumpur, Malaysia.